2007
DOI: 10.1152/jn.00471.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Soleus H-Reflexes During Gait in Children With Cerebral Palsy

Abstract: Hodapp M, Klisch C, Mall V, Vry J, Berger W, Faist M. Modulation of soleus H-reflexes during gait in children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 22 publications
3
35
1
Order By: Relevance
“…It's worth mentioning that the high variability of values for all joints among children with diplegic CP were also observed in the study by Stott et al (2) and lead to consider an immaturity of movements, corroborating the findings of Hodapp et al (33) and Prosser et al (15). Immaturity in the gait for the DG would be a consequence of encephalic lesion and inhibition of the tonic muscular development that occurs over the children's growth (33).…”
Section: Angular Variablessupporting
confidence: 74%
See 1 more Smart Citation
“…It's worth mentioning that the high variability of values for all joints among children with diplegic CP were also observed in the study by Stott et al (2) and lead to consider an immaturity of movements, corroborating the findings of Hodapp et al (33) and Prosser et al (15). Immaturity in the gait for the DG would be a consequence of encephalic lesion and inhibition of the tonic muscular development that occurs over the children's growth (33).…”
Section: Angular Variablessupporting
confidence: 74%
“…Immaturity in the gait for the DG would be a consequence of encephalic lesion and inhibition of the tonic muscular development that occurs over the children's growth (33).…”
Section: Angular Variablesmentioning
confidence: 99%
“…In contrast to control children, there was no correlation between age and stretch reflex size in the children with CP. Hodapp et al (2007b) similarly observed that the soleus H reflex evoked in stance during gait did not show an age-related reduction as in control children. As they suggested, this may reflect a lack of maturation of the corticospinal tract in the children with CP.…”
Section: Age-related Decline In M1 Response Late In Stance In Controlmentioning
confidence: 53%
“…Other evidence of corticospinal tract damage demonstrated that children with CP do not show the tonic suppression of H-reflexes during the stance phase in gait observed in children developing typically [20]. The suppression of the H-reflex happens as the corticospinal tract matures, and it has been hypothesized that the immature pattern persists in children with CP due to corticospinal tract damage [20].…”
Section: Central Sitesmentioning
confidence: 99%
“…The suppression of the H-reflex happens as the corticospinal tract matures, and it has been hypothesized that the immature pattern persists in children with CP due to corticospinal tract damage [20]. In a laboratory setting, individuals with CP may appear less fatigable than the general population as a result of the inability of the descending tracts to fully transmit the signal to the muscles needed to produce a maximal contraction.…”
Section: Central Sitesmentioning
confidence: 99%